ANALISIS PENGARUH RESAPAN AIR LAUT TERHADAP INTRUSI AIR SUMUR GALI DESA JANGKANG KABUPATEN BENGKALIS - Nurul Izati; Riad Syech (Komunikasi Fisika Indonesia, 2020)
This study aims to determine how much the pollution level of wells digging to the distance of wells from the coast by analyzing the values of the conductivity, salinity, pH and heavy metals such as Lead(Pb), Iron(Fe) and Manganese(Mn). The method used was purposive sampling with number of sample are 10 sample points with variation distance ± 100 m. Conductivity measurements were carried out in two ways, namely using a conductivitimeter and Wheatstone bridge. The measurement results using conductivity meter indicate that the average conductivity value of a well water sample is 125.50 - 80.04 μS/cm while the comparison using the Wheatstone bridge method has an error percentage value of 6.12 %. The salinity has values ranged from 0.112 - 0.093 ‰ which is classified as fresh water. The measurement of pH values shows indications of pollution, due to water classified as acid with a pH value ranging from 3.1 - 4.1. The measurement of the value of Iron(Fe) and Manganese(Mn) does not indicate water pollution due to heavy metals with an average concentration of Iron(Fe) 0.3697 mg/l and Manganese(Mn) 0.0391 mg/l. Comparison of the salinity and conductivity values to the well distance from the coast does not show relation that correlates with seawater intrusion in Mekar Indah Vilage.